Habitat predictive modelling and geospatial database of Batagur affinis (Contor, 1847) in Kemaman River, Malaysia - Mohd Yusof, Fasihah (2018)
A freshwater turtle species, southern river terrapin or Batagur affinis is listed as a Critically Endangered species in International Union for Conservation of Nature (IUCN) Red List for Threatened Species. Hence, in purpose to achieve the cost effective and well-guided future monitoring and habitat rehabilitation program, the understanding on their optimum physical habitat requirement is highly paramount. Parallel to that mission, one of the main objectives of this research is to understand their physical habitat requirements and habitat preferences of this keystone species to maintain its sustainability inside the lower part of Kemaman River. The habitat suitability index (HSI) for six main physical parameters were constructed and the optimum flow for B. affinis was proposed by employing the concept of Environmental Flow Assessment (EFA) using habitat modeling simulations approach. Based on the developed HSI, the highest preference range for velocity and depth were between 0.1-0.2 m/s and 2.0-3.0 m respectively, for the nesting bay sediment grain size, the highest preference index recorded were between 0.06 – 2.0 mm, which classified as sandy sediment. Next, for degree of nesting bank slope, the highest preference index recorded were between 7-9o with average of 8.55o. In addition, for canopy coverage preferences aspect, approximately about 3 to 4 percent of coverage recorded the highest preference for B. affinis’ roaming area. However, the curve shows no pattern of preference for total suspended solid parameter (TSS). For second objective, based on habitat simulation, the maximum Area Weighted Suitability, AWS of the habitat availability for B. affinis is 32.439 m2/m at a simulated flow of 26.84 m3/s while the minimum AWS is 3.606 m2/m at flow of 4.474 m3⁄s. AWS values decrease at simulated flow of 32.439 m2/m and continuously decrease while the flow is increasing. The AWS values are then been categorized into three different group which are Optimum Available Range (OAHR), Degrading Available Habitat Range (DAHR) and Severely Degrading Available Habitat Range (SDAHR). Based on habitat simulation, the OAHR for B. affinis is between 26.84 - 30.46 m3/sec. This is the recommended flow that should be retained in Kemaman River to ensure the habitat availability and sustainability of this species. While, the value of DAHR is <26.84 m3/sec, and depleting of discharge within this flow ranges will cause a decreasing in Area Weighted Suitability (AWS). However, within this range, the rate of habitat deterioration is moderate. Other than that, the value of SDAHR is >30.46 m3/sec, and within this range, significant deterioration in AWS are resulted from only subtle changes in stream flow. For third objectives, the developed geospatial database will help in future species conservation effort as the information can be kept in a visual map presentation in a more interactive and manageable manners which subsequently can help to save a lot of information-searching time and align strategies in a more precise result-oriented basis.